2019
DOI: 10.1002/humu.23898
|View full text |Cite
|
Sign up to set email alerts
|

From incomplete penetrance with normal telomere length to severe disease and telomere shortening in a family with monoallelic and biallelic PARN pathogenic variants

Abstract: PARN encodes poly(A)-specific ribonuclease. Biallelic and monoallelic PARN variants are associated with Hoyeraal-Hreidarsson syndrome/dyskeratosis congenita and idiopathic pulmonary fibrosis (IPF), respectively. The molecular features associated with incomplete penetrance of PARN-associated IPF have not been described. We report a family with a rare missense, p.Y91C, and a novel insertion, p.(I274*), PARN variant. We found PARN p.Y91C had reduced deadenylase activity and the p.(I274*) transcript was depleted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 68 publications
2
16
0
1
Order By: Relevance
“…In our study, consistent with previous reports, a compound heterozygous mutation was eventually confirmed in P1 with HHS characteristics, including one site mutation (c.204G > T, p.Q68H) that has been reported to be pathogenic and the other deletion mutation (c.178‐245del, p.K59fs*6) causing only partial ND1(N‐terminal nuclease domains 2) of PARN left and a dramatical change in the protein structure. At the same time, his mother, a carrier of monoallelic PARN mutation, showed no obvious clinical phenotype with short telomere, which is consistent with the conclusion of incomplete penetrance of PARN ‐associated disease in previous study 25 . Mutations in DKC1 were the first disease‐causing mutations identified and are associated with the classic DC phenotype.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, consistent with previous reports, a compound heterozygous mutation was eventually confirmed in P1 with HHS characteristics, including one site mutation (c.204G > T, p.Q68H) that has been reported to be pathogenic and the other deletion mutation (c.178‐245del, p.K59fs*6) causing only partial ND1(N‐terminal nuclease domains 2) of PARN left and a dramatical change in the protein structure. At the same time, his mother, a carrier of monoallelic PARN mutation, showed no obvious clinical phenotype with short telomere, which is consistent with the conclusion of incomplete penetrance of PARN ‐associated disease in previous study 25 . Mutations in DKC1 were the first disease‐causing mutations identified and are associated with the classic DC phenotype.…”
Section: Discussionsupporting
confidence: 86%
“…Posttranslational modifications also have the potency to modify the protein‐binding network of PARN (Duan et al, 2019; Reinhardt et al, 2010). Previous transcriptome analysis indicated that PARN knockdown has a significant impact on the expression a subset of genes including mRNA metabolism, cell migration and adhesion, DNA replication, recombination and repair, cell growth and proliferation (Devany, Zhang, Park, Tian, & Kleiman, 2013; J. E. Lee et al, 2012), and on the biogenesis of miRNAs and small nuclear RNAs (Berndt et al, 2012; Boele et al, 2014; Dhanraj et al, 2015; Dodson et al, 2019; Harwig, Herrera‐Carrillo, Jongejan, van Kampen, & Berkhout, 2015; Katoh, Hojo, & Suzuki, 2015; Moon et al, 2015; Shukla et al, 2019; Yoda et al, 2013; X. Zhang et al, 2015). Therefore, DNA damage induces a highly complicated action of PARN to globally modulate the fates of both DDR‐responsive mRNAs and noncoding RNAs, which will be described in detail below.…”
Section: Parn In Ddr and Genomic Stabilitymentioning
confidence: 99%
“…Besides miRNA, PARN also acts as a 3′‐end trimmer of snoRNAs (Berndt et al, 2012; Dhanraj et al, 2015; Duan et al, 2019; Son, Park, & Kim, 2018), telomere RNA (Benyelles et al, 2019; Boyraz et al, 2016; Deng et al, 2019; Dhanraj et al, 2015; Dodson et al, 2019; Mason & Bessler, 2015; Moon et al, 2015; Nguyen et al, 2015; Roake et al, 2019; Shukla, Schmidt, Goldfarb, Cech, & Parker, 2016; Stuart et al, 2015; Tummala et al, 2015), rRNA (Benyelles et al, 2019; Ishikawa et al, 2017; Montellese et al, 2017; Nieto et al, 2020), and Y RNA (Shukla & Parker, 2017). It is worth noting that a PARN homologue, PARN‐like domain‐containing 1 (PNLDC1) contributes to piRNA biogenesis in silkworms, Caenorhabditis elegans , and mammalians (Ding et al, 2017; Izumi et al, 2016; Tang, Tu, Lee, Weng, & Mello, 2016).…”
Section: Parn In Ddr and Genomic Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Deleterious effects of heterozygous loss of IBMF genes that mediate clinical phenotypes with biallelic inactivation (eg, genes associated with FA) also remain incompletely defined. 1,18 Clarifying genotype-phenotype correlation and disease penetrance is vital to helping patients and families make informed decisions about therapeutic options such as hematopoietic stem cell transplantation or family planning. As molecular diagnostic capabilities have increased genetic testing, there is an urgent need to improve our understanding of the significance of putative pathogenic variants in IBMF genes.…”
Section: Introductionmentioning
confidence: 99%